2019
DOI: 10.1371/journal.pone.0225999
|View full text |Cite
|
Sign up to set email alerts
|

On-site blood culture incubation shortens the time to knowledge of positivity and microbiological results in septic patients

Abstract: Onsite blood culture incubation shortens the time to knowledge of positivity and microbiological results in septic patients. PLoS ONE 14(12): e0225999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
1
18
7
Order By: Relevance
“…Our research suggested that satellite blood culture signi cantly reduces turnaround time including TI and TK(P < 0.001), which is similar with the previous studies [8,9]. In our study, compared with medical microbiology laboratory blood culture group, TI was reduced by 3.02 h and TK was reduced by 9.76 h in satellite blood culture group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our research suggested that satellite blood culture signi cantly reduces turnaround time including TI and TK(P < 0.001), which is similar with the previous studies [8,9]. In our study, compared with medical microbiology laboratory blood culture group, TI was reduced by 3.02 h and TK was reduced by 9.76 h in satellite blood culture group.…”
Section: Discussionsupporting
confidence: 89%
“…However, when it comes to TA, the study didn't demonstrate that satellite blood culture is better than medical microbiology laboratory blood culture (p = 0.056),although the median time from specimen collection to adjust antibiotic was reduced by 23.08 h in satellite blood culture group. It is contrary to Schwarzenbacher's ndings [9]. Small sample size maybe the main reason for it.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Between 30 and 50% of patients with suspected sepsis or shock have positive blood cultures [ 14 ] and blood stream infections are associated with 14–37% mortality [ 15 , 16 ]. Schwarzenbacher et al recently commented that only 20% of laboratories in Europe offer 24 h microbiology services, thereby adding additional challenges for the timely reporting of results (COVID-19 or other pathogens) [ 17 ]. Idelevich et al reported only 13% of laboratories from 25 European countries provide 24 h microbiology service [ 18 ].…”
mentioning
confidence: 99%